Comprehensive, integrated approaches to suicide prevention: practical guidance. (20th December 2017) - Caine, Eric D; Reed, Jerry; Hindman, Jarrod; Quinlan, Kristen
Abstract : Background: Efforts in the USA during the 21st century to stem the ever-rising tide of suicide and risk-related premature deaths, such as those caused by drug intoxications, have failed. Based primarily on identifying individuals with heightened risk nearing the precipice of death, these initiatives face fundamental obstacles that cannot be overcome readily. Objective: This paper describes the step-by-step development of a comprehensive public health approach that seeks to integrate at the community level an array of programmatic efforts, which address upstream (distal) risk factors to alter life trajectories while also involving health systems and clinical providers who care for vulnerable, distressed individuals, many of whom have attempted suicide. Conclusion: Preventing suicide and related self-injury morbidity and mortality, and their antecedents, will require a systemic approach that builds on a societal commitment to save lives and collective actions that bring together diverse communities, service organisations, healthcare providers and governmental agencies and political leaders. This will require frank, data-based appraisals of burden that drive planning, programme development and implementation, rigorous evaluation and a willingness to try-fail-and-try-again until the tide has been turned.